The Wheat Snn7 Gene Confers Susceptibility on Recognition of the Parastagonospora nodorum Necrotrophic Effector SnTox7. Issue 2 (1st July 2015) - Shi, Gongjun; Friesen, Timothy L.; Saini, Jyoti; Xu, Steven S.; Rasmussen, Jack B.; Faris, Justin D.
Abstract : Parastagonospora (syn. ana, Stagonospora; teleo, Phaeosphaeria ) nodorum (Berk.) Quaedvleig, Verkley & Crous is a necrotrophic fungal pathogen that causes the disease Septoria nodorum blotch (SNB) on wheat ( Triticum aestivum L. subsp. aestivum ). The fungus produces necrotrophic effectors (NEs) that cause cell death when recognized by corresponding host genes, which ultimately leads to disease. To date, eight host gene–NE interactions have been described in the wheat– P. nodorum system. Here, we report the identification and partial characterization of a ninth interaction involving a P. nodorum ‐produced NE designated SnTox7 and a wheat gene designated Snn7 . SnTox7 is a small protein with an estimated size less than 30 kDa and largely resistant to heat and chemical treatment. The Snn7 gene governs sensitivity to SnTox7 and was delineated to a 2.7‐cM interval on the long arm of wheat chromosome 2D. The Snn7 –SnTox7 interaction explained 33% of the variation in disease among a segregating population, indicating that the interaction plays a prominent role in the development of SNB. The Snn7 sensitivity allele was identified in the hexaploid wheat cultivar Timstein, but evaluation of a set of 52 hexaploid lines of diverse origin indicated that few genotypes harbored a functional Snn7 allele, thus indicating that Snn7 is relatively rare. The identification of the Snn7 –SnTox7 interaction adds to our knowledge of the wheat– P. nodorum pathosystem, which has become a model for necrotrophic specialist fungal pathogens and their interactions with plants leading to necrotrophic effector‐triggered susceptibility.